Developing Assessment for Learning-Oriented Worksheets to Improve Student Learning Outcomes in Thermochemistry - Aisy, Adib Al; Muchlis, Muchlis (Universitas Pendidikan Mandalika, 2025)
Abstract:Â This study aims to develop assessment-for-learning-oriented worksheets suitable for improving students' learning outcomes in thermochemistry. The study was conducted at SMAN 14 Surabaya with 34 students as the respondents. The research method used was Research and Development (R&D) with the 4D model, limited to the development stage. The criteria for suitable student worksheets were evaluated based on validity, practicality, and effectiveness. Data analysis techniques for validity were conducted using a validation questionnaire method, while practicality was assessed through observation and student response questionnaires. Effectiveness was evaluated using a test method. The validity results obtained a median score of 4 from the three validators, indicating valid criteria. The practicality data showed that student responses to the worksheets received a percentage of 96.7% in the good category. Observations of relevant student activities yielded a percentage range of 84% to 100%. Effectiveness data were obtained from the pretest and posttest scores, which were then statistically tested using the Wilcoxon Test and N-Gain score. The significance value test resulted in 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. N-Gain analysis showed that 31 students were in the high category and 3 in the moderate category. Based on validity, practicality, and effectiveness, the student worksheets oriented toward assessment for learning are suitable for use in improving student learning outcomes in thermochemistry.